2023
DOI: 10.1097/gox.0000000000005034
|View full text |Cite
|
Sign up to set email alerts
|

Advances on Capsular Contracture—Prevention and Management Strategies: A Narrative Review of the Literature

Pietro Susini,
Giuseppe Nisi,
Diletta Maria Pierazzi
et al.

Abstract: Background: Capsular contracture (CC) is the most relevant complication of both aesthetic and reconstructive breast implant surgery. For many years, experimental and clinical trials have attempted to analyze CC risk factors, clinical features, and appropriate management strategies. It is commonly accepted that a multifactorial etiology promotes CC development. However, the heterogeneity in patients, implants and surgical techniques make it difficult to suitably compare or analyze specific factors. As a consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…[17] In the field of facial cosmetic procedures, this approach is a key tool for achieving personalized and culturally sensitive results for different patients. [27][28][29][30][31][32] Moreover, according to our experience, lipofilling associated with rhinoplasty promotes antiinflammatory effects, aiding in facial recovery and optimizing the overall outcome for enhanced patient well-being. [11][12][13][14] Our study retrospectively analyzed patients who underwent open augmentation Rhinoplasty and Centrofacial Lipofilling (ARCL) in Rio de Janeiro between January 2019 and December 2022.…”
Section: Discussionmentioning
confidence: 99%
“…[17] In the field of facial cosmetic procedures, this approach is a key tool for achieving personalized and culturally sensitive results for different patients. [27][28][29][30][31][32] Moreover, according to our experience, lipofilling associated with rhinoplasty promotes antiinflammatory effects, aiding in facial recovery and optimizing the overall outcome for enhanced patient well-being. [11][12][13][14] Our study retrospectively analyzed patients who underwent open augmentation Rhinoplasty and Centrofacial Lipofilling (ARCL) in Rio de Janeiro between January 2019 and December 2022.…”
Section: Discussionmentioning
confidence: 99%
“…There are works in which it is shown that macrophages loaded with silicone play the main (central) role, stimulating fibroblasts to collagenogenesis and thus contribute to the development of capsular contracture [18,24]. Macrophages in culture can be stimulated by silicone to release interleukin-1, which is a pro-inflammatory cytokine that plays an important role in fibroblast proliferation and differentiation [18,42].…”
Section: Discussionmentioning
confidence: 99%
“…Capsular contracture appears to be directly impacted by factors such as the implant’s content (silicon or a saline solution), implant’s placement (submuscular or subglandular), implant’s surface texture (smooth or textured) and bacterial infection. Moreover, patients undergoing more intricate procedures, like breast reconstruction, tend to exhibit higher rates of capsular contracture compared to those undergoing simpler augmentation [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methods of prevention, apart from those related to implant texture and content, include the techniques used for implant placement, the surgical approach, the placement site and method, the use of drainage, and the wound closure method [ 17 , 20 , 21 ]. Adams et al consider antibiotic prophylaxis to be extremely important, proposing the intraoperative washing of the implant pocket with a triple combination of antibiotics, a procedure proven to be highly effective in preventing capsular contracture [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%